(untitled) (Shahroud Journal of Medical Sciences, 2021)
Background: This study aimed to investigate the effectiveness of cognitive therapy based on mindfulness training on reducing social anxiety and increasing the self-esteem of students with learning disabilities. Methods: This study was a quasi-experimental trial with a pretest-posttest design along with a control group. The statistical population included all male students with learning disabilities in the 2018-2019 academic years, in the fourth to sixth grades of Isfahan. The sample consisted of 30 people who were randomly divided into two groups of control and experimental (15 people in each group). The research instruments included the Libovitz social anxiety questionnaire and Cooper-Smith self-esteem questionnaire. Data were analyzed using SPSS version 22 according to the analysis of covariance (ANCOVA). Results: The results showed that mindfulness-based cognitive therapy was effective in reducing social anxiety of students with learning disabilities (Pvalue<0.01). Also, mindfulness-based cognitive therapy was effective in increasing the self-esteem of students with learning disabilities (Pvalue<0.01). Conclusions: Based on the results, mindfulness-based cognitive therapy can reduce social anxiety in students with learning disabilities and increase their self-esteem. Keywords: Cognitive therapy, Social anxiety, Self-esteem, Learning disabilities.